PEMINATAN PENGOBATAN TRADISIONAL DI LINGKUNGAN PANDAI BESI KECAMATAN SEKARBELA KOTA MATARAM - Husnul Jannah; Sri Nopita Primawati (Bioscientist : Jurnal Ilmiah Biologi, 2019)
The purpose of this research is to find out the types and what medicinal plants are used by the people in Karang Pule Hamlet. Data retrieval in this study through two approaches, namely field research to get primary data and then enriched through secondary data. Primary data collection is carried out by involving the community through interviews with local community groups and individual members of the community. The selection criteria are based on the ability and practice of traditional medicine that conducted by informants. In collecting data, the interview technique used is open ended. This data collection technique is also used to explore knowledge systems about the diversity of traditional medicinal plant species, how to manage them, use them as well as to maintain the interest of the medical community using medicinal plants. Obtained types of medicinal plants that are used by the community in the Iron Pande Environment include Red Onion, Betel, Ginger, Castor Leaves, Guava, Turi Leaves, Lime, Sager, Banten, Kencur, Galangal, Turmeric, Cat Mustache, Horse Whip, Tongue Crocodile, Sondak / Pumpkin, Papaya, Blimbing, Cinnamon, Temulawak, Celery, Soursop Leaves, and Lemongrass. So, it can be concluded that medicinal plants can be beneficial to improve the health status of Karang Pule community.